Aplikasi Regresi Cox Pada Selang Kelahiran Anak Pertama di Provinsi Sumatera Selatan - Faruk, Alfansi (Jurnal Matematika; Vol 7 No 1 (2017), 2017)
The birth interval of first child is one example of survival analysis. The objective of this research is to determine the best Cox regression model that describes the impact of several factors to the birth interval of first child in South Sumatra Province. The data were based on the Indonesia Demographic and Health Survey (IDHS) 2012. In this work, we included four factors, i.e. the age of the mother, mother’s highest education, place of residence, and wealth index. Based on several tests that have been conducted, the factors which significantly affect the survival time were the age of the mother, mother’s highest education (junior high school), and wealth index (middle and very rich). Keywords : Cox regression,  IDHS, The birth interval